Effects of secondary hyperparathyroidism treatment on hemoglobin levels and erythropoietin doses in hemodialysis patients - Massimetti, Carlo; Bellasi, Antonio; Feriozzi, Sandro (Journal of Clinical Nephrology, 2021)
Aim: Secondary hyperparathyroidism (SHPT) is an often underestimated cause of anemia in hemodialysis (HD) patients. The aim of this study was to assess the effect of pharmacological correction of SHPT on anemia and erythropoiesis-stimulating agents (ESAs) need. Methods: For the purpose of this retrospective pre-post observational study, we selected 55 HD patients, receiving HD at one single center, in the period from January 2005 to December 2020. The follow-up (F-U) lasted 12 months. The selection criteria were parathormone (PTH) levels > 300 pg/ mL, and hemoglobin (Hb) levels < 11 g/dL, despite treatment with ESAs. Parametric and non-parametric tests were used when appropriate. In the light of exploratory nature of the study, the limited sample size and in consideration of the pre-post-design, no further adjustment for potential confounders is performed. Results: The hemoglobin levels throughout the study were correlated to serum PTH (r = -.257, p < 0.01). At the end of the F-U, in the 40 patients whose PTH levels decreased ≥ 30% (responders group) Hb levels increased from 10.3 ± 0.5 g/dL to 12.2 ± 1.1 g/dL (p < 0.001), and ESAs doses decreased from 141 ± 101 IU/kg/b.w./week to 94 ± 76 IU/kg/b.w./week (p < 0.05). On the contrary, in the non-responders group Hb levels did not change 10.3 ± 0.5 gr/dL at baseline and 10.1 ± 1.1 gr/dL at F-U (P = NS), and the mean doses of ESAs increased from 144 ± 75 IU/kg/b.w./week to 218 ± 145 IU/kg/b.w./week (P = NS). Conclusion: Adequate control of SHPT is associated with concomitant improvement of anemia and decrease in ESAs need. Future endeavors are required to confirm these preliminary results.